A circularly polarized Fabry‐Perot resonant cavity antenna using frequency selective surface‐based partial reflecting surface. Issue 8 (4th May 2021) - Yang, Chunfeng; Zhu, Xiao‐Wei; Liu, Pengfei
Abstract: This paper designed a circularly polarized (CP) Fabry‐Perot (F‐P) resonant cavity antenna which utilized a frequency selective surface (FSS)‐based partial reflecting surface (PRS). The loading thin single‐layer FSS‐based PRS is composed of patches on the top layer of the substrate and square loop slots on the bottom. With the obtained positive slope for the reflection coefficient phase of the loading PRS, the operating bandwidth of the F‐P resonant cavity antenna is expanded. In order to further expand the bandwidth, we introduced a sequentially rotating feeding network to excite a 2 × 2 CP patch array, which is used as a feed source for the resonant cavity antenna. By experiment, the actual measured |S11| < −10 dB impedance bandwidth is 26.9%, while the 3‐dB axial ratio (AR) bandwidth is approximately 17%. A maximum gain of 15.4 dBic and a radiation efficiency is 86.8% are achieved, which indicate that the proposed antenna is a promising candidate for CP communication applications.